Marketing Mix by Bed Occupancy Ratio (BOR) - Abdul Muhith; M. Himawan Saputra; Nursalam Nursalam (Universitas Airlangga, 2013)
Introduction: Bed Occupancy Ratio (BOR) in RSI Arafah Mojosari during the last three years are at under ideal rate and the lowest of the three existing hospitals in the area of Mojosari. The purpose of this study was to determine the relationship marketing mix with Bed Occupancy Ratio in RSI Arafah Mojosari.Methods: This research uses analytic methods with crossectional approach. Variables in the study is marketing mix and Bed Occupancy Ratio (BOR). The population in this study were all patients hospitalized in the RSI Arafah Mojosari. Samples amounted 44 respondents taken by the Stratified random sampling technique. Data were collected using the questionnaire and analyzed using Fisher's Exact test.Result: The results obtained more than 50% of respondents (59.1%) rate well against the marketing mix is developed by the hospital management and the majority of respondents (79.5%) are in the treatment room that has a number BOR is not ideal. Fisher Exact test test results obtained probabililty value=0.02<0.05 so that H0 is rejected, which means there is a relationship marketing mix with the Bed Occupancy Ratio in RSI Arafah Mojosari.Conclusion: Hospitals which able to develop the marketing mix very well, can attract consumers to use inpatient services at the hospital, with that BOR value will increase as the increased use of inpatient services. Hospital management must be able to formulate a good marketing mix strategy that hospital marketing objectives can be achieved. Conformity between service quality and service rates must be addressed, otherwise it extent of media promotions can attract patients to inpatient services.